Intensified nutrition interventions in antenatal care services increased consumption of iron and folic acid supplements and early breastfeeding practices in Burkina Faso: Results of a cluster-randomized program evaluation - Kim, Sunny S.; Zagré, Rock Romaric; Ouédraogo, Césaire T.; Sununtnasuk, Celeste; Ganaba, Rasmané; Zafimanjaka, Maurice G.; Tharaney, Manisha; Sanghvi, Tina; Menon, Purnima (Elsevier, 2023)
Background: Alive & Thrive supported the Government of Burkina Faso to strengthen the provision of iron-folic acid (IFA) supplementation and interpersonal counseling on maternal nutrition and breastfeeding through antenatal care (ANC) services and community-based contacts in two regions. Objectives: We assessed the impacts of intensified nutrition interventions during ANC compared with standard ANC services on intervention coverage and maternal nutrition practices. Methods: A cluster-randomized evaluation compared 40 health center catchment areas in intervention areas to 40 in control areas. Repeated cross-sectional surveys in 2019 and 2021 (960 pregnant women and 1920 women with children 0-5 months of age per survey round) provided data on impact indicators, intervention exposure and other factors. We derived difference-in-difference effect estimates (DID), adjusted for geographical clustering, for maternal dietary diversity, IFA consumption, and early breastfeeding practices. Results: More women in intervention areas had 4+ ANC visits (DID: 8.3 percentage points [pp]) and started ANC during the first trimester (DID: 10.5 pp), compared to control areas. Improvements were achieved in exposure to nutrition counseling on dietary diversity (DID: 44.4 pp), food quantity (DID: 42.9 pp), adequate weight gain (DID: 35.1 pp), and breastfeeding (DID: 25.9 pp). Women in intervention areas consumed more IFA supplements during pregnancy (DID: 21 tablets). Early initiation of and exclusive breastfeeding also improved (DID: 17.0 pp and 8.3 pp, respectively). However, dietary diversity (4 out of 10 food groups) and mean probability of adequacy of micronutrient intake (14%) among pregnant women remained low in both areas. Conclusions: Strengthening maternal nutrition interventions delivered through government ANC services was feasible and effective in improving maternal nutrition practices. Continued efforts to strengthen the delivery and use of maternal nutrition services may be required for greater behavior changes, and to address family support, social norms, and other factors to improve women’s diet during pregnancy.